Aspirin use in patients with diagnosed diabetes in the United States and China: Nationally representative analysis. (14th December 2021) - Wang, Xin; Hao, Guang; Chen, Zuo; Zhang, Linfeng; Kang, Yuting; Yang, Ying; Zheng, Congyi; Zhou, Haoqi; Chen, Lu; Wang, Zengwu; Gao, Runlin
Background: The epidemiological data on the use of aspirin in diabetic patients is very limited. The main purpose of this study is to examine the current status of aspirin use in the United States (US) and China in large representative populations. Methods: Data came from the National Health and Nutrition Examination Survey (NHANES) and China Hypertension Survey (CHS), two nationally representative cross-sectional studies. Results: The percentage of aspirin use was 73.8% in US diabetic patients with ASCVD, and the percentage of aspirin use in diabetic patients with high ASCVD risk was marginally higher in men ( p = .052), 54.5% in men and 37.1% in women. The percentages of aspirin use in diabetic patients with intermediate and low ASCVD risk were 55.1% and 35.0%, respectively. In China, the percentage of aspirin use in diabetic patients with ASCVD was 53.5%, and were 14.3%, 9.7%, and 3.2% among diabetic patients with high, intermediate, and low ASCVD risk, respectively. Conclusions: In summary, the percentage of aspirin use in primary prevention in US diabetic patients in men was higher than in women, and this percentage for primary and secondary prevention in US patients was higher than that in Chinese patients.